PENGARUH PERAWATAN KEHAMILAN ANTENATAL CARE TERHADAP KEMATIAN IBU MELAHIRKAN DI RUMAH SAKIT KABELOTA DONGGALA SULAWESI TENGAH - Siti Rahmawati (Universitas Gadjah Mada, 2016)
One of the factors of the high number for Maternal Mortality Rate (MMR) in Indonesia is caused by thelow prenatal care and assistance by healthcare workers. In Central Sulawesi, MMR is still quite high,269 per 100 thousand live births, meanwhile, the standard number of the Ministry of Health is 226 per100 thousand live births. This study aims to determine the effect of prenatal care on maternal mortalityusing retrospective studies and logistic regression data analysis. The tabulation result of the datashowed that the relationship between prenatal care and maternal mortality was significant confidencelevel of 95%. The significance of that relationship was showed by Chi-Square= 5.84 at P<0.05 or P<0.02.OR value was 2.77 at IK 95% between 1.20 to 6.41. It showed that the chances of maternal mortality inthe subjects with poor antenatal care was about 2.77 times compared with the chance of the subject tolife. The complications which occured during the delivery and the quality of aid delivery encompassedbirth attendant for implementing the “3” clean pantographs and Kala III active management. Both ofthem statistically have a significant relationship with the incidence of maternal mortality.